The youth eco-projekt in the framework of the International triennial of the graphics design "The 4th Block" - O.D. Hladun (Academy of Cognitive and Natural Sciences, 2006)
The youth eco-projekt (nomination of the sixth triennial of the ecological poster "The 4th Block") deals with the actual tasks of the contemporary art and determined its role.